The boy chums in the Florida jungle : or, Charlie West and Walter Hazard with the Seminole Indians - Ely, Wilmer Mateo (Delhi : Lector house, 2023)
"Golly! I'm getting powerful tired ob dis. Fish what just clusterers 'round youah bait an' won't bite at hit noways is jest trifling and noaccount. I reckon dey's too ornery an' too finiky anyway to be fit to eat. Well, here goes again, though hit ain't no use. I'se dun spit on mah bait fifty times, an' rubbed hit twice with my rabbit's foot, but hit doan' do a bit of good. Dey jes' look at hit an' grin like white folks at a nigger's wedding." The little ebony negro who had spoken let drop his daintily baited hook into the water again with a gesture of disgust.
Keywords: Literature & Fiction; Seminole Indians; Juvenile works